Society, Organizations and the Brain: building towards a unified cognitive neuroscience perspective - Nick Lee (Frontiers Research Topics, 2015)
This e-book brings together scholars in both the neurosciences and organizational sciences who have adopted various approaches to study the cognitive mechanisms mediating the social behavior that we see within organizations. Such an approach has been termed by ourselves, and others, as 'organisational cognitive neuroscience'. In recent years there has been a veritable increase in studies that have explored the cognitive mechanisms driving such behaviors, and much progress has been made in understanding the neural underpinnings of processes such as financial exchange, risk awareness and even leadership. However, while these studies are informative and add to our understanding of human cognition they fall short of providing evidence-based recommendations for practice. Specifically, we address the broader issue of how the neuroscientific study of such core social behaviors can be used to improve the very way that we work. To address these gaps in our understanding the chapters in this book serve as a platform that allows scholars in both the neurosciences and the organizational sciences to highlight the work that spans across these two fields. The consolidation of these two fields also serves to highlight the utility of a singular organizational cognitive neuroscience. This is a fundamentally important outcome of the book as the application of neuroscience to address economically relevant behaviors has seen a variety of fields evolve in their own right, such as neuromarketing, neuroeconomics and so forth. The use of neuro-scientific technologies,in particular fMRI, has indeed led to a bewildering (and somewhat suffocating) proliferation of new approaches, however, the speed of such developments demands that we must proceed carefully with such ventures or risk some fundamental mistakes. The book that you now hold will consolidates these new neuroscience based approaches and in doing so highlight the importance of this approach in helping us to understand human social behavior in general. Taken together the chapters provide a framework for scholars within the neurosciences who wish to explore the further the opportunities that the study of organisational behavior may provide.